Influence of upland rice mechanization on the infestation and damage of Rhopalosiphum rufiabdominale (Sasaki, 1899) (Homoptera: Aphididae) - Ferreira, Evane; Silva, José Geraldo da; Zimmermann, Francisco José P.; Silva, Daniela Rezio e (Pesquisa Agropecuaria Brasileira, 1995)
The root aphid Rhopalosiphum rufiabdominale (Sasaki, 1899) infestation and damage were studied in an experiment of upland rice mechanization using the cultivar Caiapó. The five sowing machines and the two soil preparations used showed significant differences in the percentage of infested plants and plant population. The Caiapó grain yield was estimated to have been reduced by the aphid in about 28.5%, being 15.2% associated to missing plants and 13.3% to the feebleness of the remaining plants. To reduce the insect damage, the first step is to choose an adequate sowing machine, followed by a correct soil preparation and treatment when the crop infestation shows, at the beginning of tillering and reproductive phases, respectively, 13% and 5% of the plants with aphid colonies on the roots.